Entre patrimoine et développement durable, quel avenir pour les églises paroissiales ? - Mélanie Meynier-Philip (Développement Durable et Territoires)
Within the framework of a PhD in Architecture, the research tackles the future of the parochial churches of the Lyon Saint-Étienne urban area, in a context of accelerated secularization of Western societies. Faced with an increasing desertion – disappearance of parishioners and their religious use –their use value, linked to their potential of reconversion, as well as to their affective value, carried by a heritage community, allow them to have a future. We suggest analyzing it in a global vision taking into account the problems of urban renewal, densification and sustainable development. An inventory was made of the Lyon Saint-Étienne urban area, and those case studies illustrate current practices : reconversion and demolition. Here, this research addresses the environmental issues through the renewal of the buildings that are at the origin of the development and of the memory of the urban cores and the villages.